Mitomycin-Treated Endothelial and Smooth Muscle Cells Suitable for Safe Tissue Engineering Approaches - Zakharova, Irina; Saaya, Shoraan; Shevchenko, Alexander; Stupnikova, Alena; Zhiven', Maria; Laktionov, Pavel; Stepanova, Alena; Romashchenko, Alexander; Yanshole, Lyudmila; Chernonosov, Alexander; Volkov, Alexander; Kizilova, Elena; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
In our previous study, we showed that discarded cardiac tissue from right atrial appendage and right ventricular myocardium is an available source of functional endothelial and smooth muscle cells for regenerative medicine and tissue engineering. In the study, we aimed to find out what benefits give vascular cells from cardiac explants used for seeding on vascular patches engrafted to repair vascular defects in vivo. Additionally, to make application of these cells safer in regenerative medicine we tested an in vitro approach that arrest mitotic division to avoid the potential tumorigenic effect of dividing cells. A tissue-engineered construction in the form of a patch based on a polycaprolactone-gelatin scaffold and seeded with endothelial and smooth muscle cells was implanted into the abdominal aorta of immunodeficient mice. Aortic patency was assessed using ultrasound, MRI, immunohistochemical and histological staining. Endothelial and smooth muscle cells were treated with mitomycin C at a therapeutic concentration of 10 μg/ml for 2 h with subsequent analysis of cell proliferation and function. The absence of the tumorigenic effect of mitomycin C-treated cells, as well as their angiogenic potential was examined by injecting them into immunodeficient mice. Cell-containing patches engrafted in the abdominal aorta of immunodeficient mice form the vessel wall loaded with the appropriate cells and extracellular matrix and do not interfere with normal patency. Endothelial and smooth muscle cells treated with mitomycin C show no tumorigenic effect in the SCID immunodeficient mouse model. During in vitro experiments, we have shown that treatment with mitomycin C does not lead to a decrease in cell viability. Despite the absence of proliferation, mitomycin C-treated vascular cells retain specific cell markers, produce specific extracellular matrix, and demonstrate the ability to stimulate angiogenesis in vivo. We pioneered an approach to arresting cell division with mitomycin C in endothelial and smooth muscle cells from cardiac explant, which prevent the risk of malignancy from dividing cells in vascular surgery. We believe that this approach to the fabrication of tissue-engineered constructs based on mitotically inactivated cells from waste postoperative material may be valuable to bring closer the development of safe cell products for regenerative medicine.